Driving TVET's future: The impact of perceived organizational support and transformational leadership as a moderator on academicians' job performance - Darmansah, Darlina; Omar, Siti Nur Zahirah; Che Cob, Che Mohd Syaharuddin (Journal of Islamic, Social, Economics and Development, 2025)
The moderating effect of transformational leadership between perceived organizational support (POS) and job performance in Technical and Vocational Education and Training (TVET) institutions which are pivotal to Malaysia’s National TVET Policy 2030 and the Eleventh Malaysia Plan has been explored in this paper. This research explores how academic leaders in TVET institutions can cultivate an innovative and high-performance culture in the face of heavy workloads, as Malaysia moves towards lifting workforce readiness and meeting industry needs. Based on the Job Demands-Resources (JD-R) model, the study focuses on POS, which is perceived organizational support that is academicians' perceptions of organizational care and support as a valuable resource for surmounting workplace challenges. Findings show that transformational leadership substantially improves the positive relationship between POS and job performance particularly in high workload context. The study also shows that increased organizational support leads to enhanced job performance through enhancing motivation and engagement of academicians. Finally, the paper concludes that transformational leadership can enhance organizational support and consequently enhance academicians' job performance, engagement and motivation. These insights are important for TVET leaders and policymakers, providing actionable steps for TVET players to strengthen the sector and make it relevant to the global labour market, in order to maintain a future ready and innovative workforce for Malaysia.